THE RELATIONSHIP BETWEEN PARENTING PATTERNS OF MOTHERS AS DAILY LABOR PROFESSIONS (ART) WITH THE PROSOCIAL BEHAVIOR OF PRESCHOOL CHILDREN IN CIRENDEU VILLAGE, SOUTH TANGERANG CITY IN 2024 (Jurnal Kesehatan STIKes IMC Bintaro, 2025)
Background: Children's prosocial behavior can be influenced by various factors, one of which is parenting patterns and the role of the family as a model and source of reference for prosocial behavior. Parenting patterns play an important role in aspects of child development including prosocial behavior, because the first environment and first educator of a child is the family or a mother. Research Objective: To analyze the Relationship between Parenting Patterns of Daily Laborer (Art) Mothers and Prosocial Behavior of Preschool Children in RT.003/RW.03 Cirendeu Village, South Tangerang in 2024. Research design: used is quantitative with a Cross-sectional design. Sample: This study consisted of 60 respondents with a probability sampling type with a simple random sampling technique. Research Results: Based on the results of the Chi-Square alternative test, namely the Fisher's Exact test, the p value = 0.002 (p